Composite hydrogel lithium ion sieve and preparation method thereof

The H2TiO3@PAM composite hydrogel lithium ion sieve prepared by embedding H2TiO3 in polyacrylamide (PAM), the shortcomings in adsorption capacity and recycling of titanium-based lithium ion sieve were solved, and efficient lithium ion capture and recycling were achieved.

CN119838552AActive Publication Date: 2025-04-18NANJING TECH UNIV

Patent Information

Application Number
CN202411828987.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-04-18
Estimated Expiration
2044-12-12

Smart Images

  • Figure CN119838552A_ABST
    Figure CN119838552A_ABST
Patent Text Reader

Abstract

The invention provides a composite hydrogel lithium ion sieve and a preparation method thereof, and belongs to the technical field of lithium ion sieve adsorption. The catalyst is characterized in that the active component of the ion sieve is H2TiO3, the binder is polyacrylamide (PAM), and the ion sieve is uniformly dispersed in the polyacrylamide. The composite lithium ion sieve is used for selective adsorption extraction of lithium ions in low-concentration geothermal water, oil and gas field water, salt lake brine and seawater. The H2TiO3 and PAM composite lithium ion sieve provided by the invention has the advantages of high adsorption capacity, good structural stability, high selectivity for salt lake brine with a high magnesium-lithium ratio, easiness in separation of the composite ion sieve from a liquid solution and good regeneration repeatability, and has a good industrial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ion sieve adsorption, and in particular to a composite hydrogel lithium ion sieve and a preparation method thereof, and application of the composite hydrogel lithium ion sieve in the adsorption and extraction of liquid lithium resources. Background Art

[0002] Metallic lithium and its compounds are highly valued as strategic resources in the fields of national defense, energy, batteries, and metallurgy due to their excellent physical and chemical properties. In recent years, due to technological advances and the increasing demand for renewable clean energy, the consumption of lithium, especially for batteries, has been on the rise. However, the supply of lithium resources lags behind the growing demand.

[0003] Titanium-based lithium ion sieves (Ti-LIS) are widely studied adsorbents that exhibit high selectivity for lithium and high cycling performance. These sieves have attracted increasing attention from researchers. Compared with manganese-based ion sieves, titanium-based ion sieves have higher chemical stability, which is mainly attributed to their strong Ti-O bonds. Although the theoretical adsorption capacity of H2TiO3 reaches 126.9 mg g -1 However, the actual lithium adsorption capacity of Ti-LIS is much lower, mainly because of the limited exposure of active adsorption sites due to particle agglomeration. This gap between the actual adsorption capacity and theoretical adsorption capacity of titanium-based ion sieves requires the optimization of H2TiO3 adsorbent to improve its adsorption capacity.

[0004] Hydrogels have attracted increasing attention in fields such as biomedical engineering and environmental research due to their three-dimensional network structure, softness, and water-rich properties (Chemical reviews, 2020, 120, 7642-7707). For lithium ion sieves, these properties allow the liquid to fully diffuse in the hydrogel and contact the active sites, thereby promoting Li + desorption and improve the adsorption rate and performance. Polyacrylamide (PAM) has good hydrophilicity, which is mainly due to the polar amide group (-CONH2) in its molecular structure interacting with water molecules through hydrogen bonds (Journal of Central South University of Technology, 2008, 15, 443-446.). H2TiO3 with good hydrophilicity is more likely to form hydrogen bonds with water molecules, thereby promoting the diffusion of lithium ions from water to the sieve holes and enhancing the adsorption effect. The hydrophilic surface can effectively reduce the resistance of water molecules during the adsorption process and improve the capture rate of lithium ions.

[0005] Based on the existing technology, titanium ion sieves have the disadvantages of slow adsorption rate and too fine particles to be fully recycled, which is not conducive to industrial production. For hydrogel lithium ion sieves prepared with polyacrylamide as the support, the design and development of lithium ion sieves with high hydrophilicity and full recycling and reuse has industrial significance and social value. Summary of the invention

[0006] The purpose of the present invention is to provide a H2TiO3@PAM composite hydrogel lithium ion sieve in order to improve the deficiencies of the prior art; another purpose of the present invention is to provide a method for preparing the above-mentioned ion sieve.

[0007] The technical solution adopted by the present invention is: a H2TiO3@PAM composite hydrogel lithium ion sieve, characterized in that the composite hydrogel lithium ion sieve uses polyacrylamide PAM as a binder, and the powdered active component H2TiO3 is embedded in PAM to solve the problem that the powdered particles are lost and difficult to recover; wherein the mass fraction of H2TiO3 in H2TiO3@PAM is 13.8%-24%.

[0008] Preferably, the active component is the delithiation product H2TiO3 of the Li2TiO3 lithium ion sieve precursor, and the support is polyacrylamide PAM; preferably, the Li2TiO3 is a typical monoclinic β-Li2TiO3.

[0009] The present invention also provides a method for preparing the composite hydrogel lithium ion sieve, the specific steps of which are:

[0010] H2TiO3 and deionized water are added to a beaker and stirred evenly to obtain a suspension; then, a viscosity modifier is added to the suspension, stirred thoroughly, and then acrylamide and N,N'-methylenebisacrylamide are added at the same time. After stirring thoroughly, a catalyst and an initiator are added, and after stirring evenly, the mixture is placed in an oven for heating and polymerization to obtain a composite hydrogel; then the hydrogel is cultured in distilled water, and the water is changed every day to finally obtain H2TiO3@PAM.

[0011] Preferably, the mass fraction of H2TiO3 in the suspension is 16-30%. Preferably, the viscosity modifier is polyvinyl alcohol, chitosan or sodium alginate; the mass ratio of the viscosity modifier to the suspension is (0.002-0.010):1.

[0012] Preferably, the mass ratio of acrylamide to the suspension is (0.14-0.18): 1. Preferably, the molar ratio of N,N'-methylenebisacrylamide to acrylamide is (0.0005-0.0040): 1.

[0013] Preferably, the initiator is potassium persulfate, sodium persulfate, or ammonium persulfate; and the molar ratio of the initiator to acrylamide is (0.015-0.051):1.

[0014] Preferably, the catalyst is triethanolamine or tetramethylethylenediamine; the molar ratio of the catalyst to acrylamide is (0.005-0.007):1.

[0015] Preferably, the polymerization reaction temperature is (20-70)°C, the reaction time is 3-5h, and the culturing in distilled water is preferably 6-8 days.

[0016] The polyacrylamide PAM reaction equation is:

[0017]

[0018] Beneficial effects:

[0019] Compared with the prior art, the present invention has the following advantages:

[0020] 1. The present invention adopts polyacrylamide PAM as a binder for H2TiO3 powder molding for the first time, making full use of the abundant amide groups on the surface of polyacrylamide PAM and the high porosity of its network structure to improve the hydrophilicity of β-H2TiO3, thereby increasing the adsorption capacity and adsorption efficiency.

[0021] 2. The present invention utilizes in-situ polymerization reaction to embed H2TiO3 in polyacrylamide PAM, which has the advantages of simple operation and low cost. Compared with other molding methods, the hydrogel molding method has the advantages of low mass transfer resistance and high adsorption capacity. As a composite ion sieve adsorbent, it has broad application prospects in the field of continuous lithium extraction from salt lake brine.

[0022] 3. Compared with granulation molding, the hydrogel lithium ion sieve prepared by combining polyacrylamide PAM and H2TiO3 has a rich network structure and high hydrophilicity, which reduces the mass transfer resistance of lithium ion sieve adsorption, thereby improving the adsorption efficiency.

[0023] 4. The H2TiO3@PAM composite hydrogel lithium ion sieve prepared by the present invention is rich in functional groups such as hydroxyl groups and amide groups, which is conducive to full contact with the solution. It has high adsorption selectivity for salt lake brine with a high magnesium-lithium ratio. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The XRD patterns of polyacrylamide PAM, H2TiO3 particles, Li2TiO3 particles, H2TiO3@PAM-1 and Li2TiO3@PAM-1 prepared in Example 1 of the present invention;

[0025] Figure 2It is the infrared spectrum of polyacrylamide PAM, H2TiO3 particles and H2TiO3@PAM-1 prepared in Example 1 of the present invention;

[0026] Figure 3 is a SEM morphology image of H2TiO3 particles prepared in Example 1 of the present invention;

[0027] Figure 4 This is a SEM morphology image of H2TiO3@PAM prepared in Example 1 of the present invention;

[0028] Figure 5 is the stress-strain curve of H2TiO3@PAM-x prepared in Examples 1, 2, and 3 of the present invention;

[0029] Figure 6 It is the stress-strain curve of H2TiO3@PAM-x prepared in Examples 1, 6, 7 and 8 of the present invention. DETAILED DESCRIPTION

[0030] The following examples are only used to illustrate the description of the best mode of implementation of the present invention, and the protection scope of the present invention is not limited to the specific implementation.

[0031] Example 1

[0032] (1) Preparation of H2TiO3@PAM

[0033] 50g of H2TiO3 suspension with a mass fraction of 30% was placed in a beaker (solution A). Then sodium alginate (0.15g, 0.68mmol) was added to solution A and stirred for 15min, and then acrylamide (8g, 112.55mmol) and N,N'-methylenebisacrylamide (0.03g, 0.19mmol) were added at the same time and stirred for another 10min to obtain solution B. Subsequently, tetramethylethylenediamine (0.1mL, 0.67mmol) and potassium persulfate (0.5g, 1.9mmol) were added to solution B and stirred for 2min, and then the mixture was placed in an oven and polymerized at 50℃ for 3h to obtain a hydrogel. The hydrogel was then cultured in distilled water for 7 days, with water changed every day, and finally H2TiO3@PAM was obtained, labeled as HTO@PAM-1, the mass fraction of H2TiO3 was 24% of the total mass of the composite hydrogel, and its tensile strength was 0.190MPa.

[0034] (2) Adsorption test

[0035] 1 g H2TiO3@PAM-1 was placed in a solution containing Li at pH 8 at 25 °C. + 、Na + , Ca 2+ , K + and Mg 2+The adsorption selectivity and saturated adsorption capacity of lithium ions were determined in 1L of salt lake brine containing ions. The initial concentrations of ions in the salt lake brine were C Li+ =116.78mg·L -1 ,C Na+ =99.45mg·L -1 ,C Ca2+ =98.65mg·L -1 ,C K+ =100.72mg·L -1 and C Mg2+ =99.73mg·L -1 .

[0036] Figure 1 XRD images of Li2TiO3, H2TiO3, H2TiO3@PAM, Li2TiO3@PAM and PAM hydrogel are shown. The characteristic peaks of Li2TiO3 are consistent with the standard XRD pattern of monoclinic β-Li2TiO3 (PDF#33-0831). Compared with H2TiO3, Li2TiO3 has new peaks and some peak shifts, especially the (-133) peak, which indicates that an ion exchange reaction occurs between hydrogen ions and lithium ions. The PAM spectrum shows a broad scattering peak from 20° to 28°, which indicates an amorphous structure. After the introduction of PAM hydrogel, the characteristic peaks of H2TiO3@PAM are consistent with those of H2TiO3. The peak intensity is reduced, which is due to the embedding of PAM in H2TiO3 or Li2TiO3 particles.

[0037] Figure 2 The infrared images of H2TiO3 particles, PAM hydrogel, and H2TiO3@PAM hydrogel are shown. The 3184 cm -1 、1648cm -1 、1607cm -1 and 1448cm -1 Characteristic peaks corresponding to NH stretching vibration, C=O stretching vibration, NH bending vibration, and CN stretching vibration were observed at 3478 cm-1 in both H2TiO3 particles and H2TiO3@PAM hydrogel. -1 The characteristic peak of OH stretching vibration at . This proves that there are hydroxyl groups (-OH) in H2TiO3@PAM. Hydroxyl groups are polar and can form hydrogen bonds with water molecules, increasing the surface free energy and thus enhancing the hydrophilicity of the material.

[0038] Figure 3 and Figure 4They correspond to the SEM images of H2TiO3 and H2TiO3@PAM-4 composite hydrogel lithium ion sieves, respectively. The morphology of H2TiO3@PAM-4 composite ion sieve is a honeycomb cross-linked structure.

[0039] Figure 5 The stress-strain curve of the material. The tensile strength of PAM hydrogel is 0.009MPa, and after adding H2TiO3 to PAM hydrogel, the tensile strength increases significantly. The maximum elongation at break of H2TiO3@PAM-1 is 267.6%, and the peak tensile strength is 0.19MPa.

[0040] Figure 6 The effect of MBA dosage on the mechanical properties of H2TiO3@PAM is shown. When the dosage of MBA is 0.03g, the tensile strength reaches a maximum value of 0.19MPa. However, with the continuous increase in the dosage of MBA, both the tensile strength and the elongation at break decrease significantly. This is because too high a cross-linking density will make the material too hard and too brittle, resulting in a decrease in tensile strength and a decrease in the material's ability to deform before breaking.

[0041] Example 2

[0042] (1) Preparation of H2TiO3@PAM

[0043] 50g of H2TiO3 suspension with a mass fraction of 16% was placed in a beaker (solution A). Then sodium alginate (0.15g, 0.68mmol) was added to solution A and stirred for 15min, and acrylamide (8g, 112.55mmol) and N,N'-methylenebisacrylamide (0.03g, 0.19mmol) were added at the same time, and stirred for another 10min to obtain solution B. Tetramethylethylenediamine (0.1mL, 0.67mmol) and potassium persulfate (0.5g, 1.9mmol) were then added to solution B, stirred for 2min, and then the mixture was placed in an oven and heated to 400°C. 50℃ The hydrogel was polymerized for 3 hours under low temperature to obtain a hydrogel. The hydrogel was then cultured in distilled water for 7 days, with water changed every day, and finally H2TiO3@PAM was obtained, labeled as HTO@PAM-2. The mass fraction of H2TiO3 was 13.8% of the total mass of the composite hydrogel, and its tensile strength was 0.051MPa.

[0044] (2) Adsorption test

[0045] 1 g H2TiO3@PAM-2 was placed in a solution containing Li at pH 8 at 25 °C. + 、Na + , Ca 2+ , K + and Mg 2+The adsorption selectivity and saturated adsorption capacity of lithium ions were determined in 1L of salt lake brine containing ions. The initial concentrations of ions in the salt lake brine were C Li+ =116.78mg·L -1 ,C Na+ =99.45mg·L -1 ,C Ca2+ =98.65mg·L -1 ,C K+ =100.72mg·L -1 and C Mg2+ =99.73mg·L -1 .

[0046] Figure 5 The stress-strain curve of the material. The maximum elongation at break of H2TiO3@PAM-2 is 190.4%, and the peak tensile strength is 0.051MPa.

[0047] Example 3

[0048] (1) Preparation of H2TiO3@PAM

[0049] 50g of H2TiO3 suspension with a mass fraction of 25% was placed in a beaker (solution A). Then sodium alginate (0.15g, 0.68mmol) was added to solution A and stirred for 15min, and then acrylamide (8g, 112.55mmol) and N,N'-methylenebisacrylamide (0.03g, 0.19mmol) were added at the same time and stirred for another 10min to obtain solution B. Subsequently, tetramethylethylenediamine (0.1mL, 0.67mmol) and 10% potassium persulfate (0.5g, 1.9mmol) were added to solution B, stirred for 2min, and then the mixture was placed in an oven and polymerized at 50℃ for 3h to obtain a hydrogel. The hydrogel was then cultured in distilled water for 7 days, with water changed every day, and finally H2TiO3@PAM was obtained, labeled as HTO@PAM-3, the mass fraction of H2TiO3 was 19% of the total mass of the composite hydrogel, and its tensile strength was 0.075MPa.

[0050] (2) Adsorption test

[0051] 1 g H2TiO3@PAM-3 was placed in a solution containing Li at pH 8 at 25 °C. + 、Na + , Ca 2+ , K + and Mg 2+ The adsorption selectivity and saturated adsorption capacity of lithium ions were determined in 1L of salt lake brine containing ions. The initial concentrations of ions in the salt lake brine were C Li+ =116.78mg·L-1 ,C Na+ =99.45mg·L -1 ,C Ca2+ =98.65mg·L -1 ,C K+ =100.72mg·L -1 and C Mg2+ =99.73mg·L -1 .

[0052] Figure 5 The stress-strain curve of the material. The maximum elongation at break of H2TiO3@PAM-3 is 248.6%, and the peak tensile strength is 0.075MPa.

[0053] Example 4

[0054] (1) Preparation of H2TiO3@PAM

[0055] 50g of H2TiO3 suspension with a mass fraction of 30% was placed in a beaker (solution A). Then sodium alginate (0.1g, 0.45mmol) was added to solution A and stirred for 15min, and then acrylamide (8g, 112.55mmol) and N,N'-methylenebisacrylamide (0.03g, 0.19mmol) were added at the same time and stirred for another 10min to obtain solution B. Tetramethylethylenediamine (0.1mL, 0.67mmol) and potassium persulfate (0.5g, 1.9mmol) were then added to solution B and stirred for 2min. The mixture was then placed in an oven and polymerized at 50°C for 3h to obtain a hydrogel. The hydrogel was then cultured in distilled water for 7 days, with water changed every day, and finally H2TiO3@PAM was obtained, labeled as HTO@PAM-4. The mass fraction of H2TiO3 was 24% of the total mass of the composite hydrogel, and its tensile strength was 0.138MPa.

[0056] (2) Adsorption test

[0057] 1 g H2TiO3@PAM-4 was placed in a solution containing Li at pH 8 at 25 °C. + 、Na + , Ca 2+ , K + and Mg 2+ The adsorption selectivity and saturated adsorption capacity of lithium ions were determined in 1L of salt lake brine containing ions. The initial concentrations of ions in the salt lake brine were C Li+ =116.78mg·L -1 ,C Na+ =99.45mg·L -1 ,C Ca2+ =98.65mg·L -1,C K+ =100.72mg·L -1 and C Mg2+ =99.73mg·L -1 .

[0058] Example 5

[0059] (1) Preparation of H2TiO3@PAM

[0060] 50g of H2TiO3 suspension with a mass fraction of 30% was placed in a beaker (solution A). Then sodium alginate (0.5g, 2.27mmol) was added to solution A and stirred for 15min, and then acrylamide (8g, 112.55mmol) and N,N'-methylenebisacrylamide (0.03g, 0.19mmol) were added at the same time and stirred for another 10min to obtain solution B. Tetramethylethylenediamine (0.1mL, 0.67mmol) and potassium persulfate (0.5g, 1.9mmol) were then added to solution B and stirred for 2min. The mixture was then placed in an oven and polymerized at 50°C for 3h to obtain a hydrogel. The hydrogel was then cultured in distilled water for 7 days, with water changed every day, and finally H2TiO3@PAM was obtained, labeled as HTO@PAM-5. The mass fraction of H2TiO3 was 24% of the total mass of the composite hydrogel, and its tensile strength was 0.129MPa.

[0061] (2) Adsorption test

[0062] 1 g H2TiO3@PAM-5 was placed in a solution containing Li at pH 8 at 25 °C. + 、Na + , Ca 2+ , K + and Mg 2+ The adsorption selectivity and saturated adsorption capacity of lithium ions were determined in 1L of salt lake brine containing ions. The initial concentrations of ions in the salt lake brine were C Li+ =116.78mg·L -1 ,C Na+ =99.45mg·L -1 ,C Ca2+ =98.65mg·L -1 ,C K+ =100.72mg·L -1 and C Mg2+ =99.73mg·L -1 .

[0063] Example 6

[0064] (1) Preparation of H2TiO3@PAM

[0065] 50g of H2TiO3 suspension with a mass fraction of 30% was placed in a beaker (solution A). Then sodium alginate (0.15g, 0.68mmol) was added to solution A and stirred for 15min, and then acrylamide (8g, 112.55mmol) and N,N'-methylenebisacrylamide (0.01g, 0.06mmol) were added at the same time and stirred for another 10min to obtain solution B. Subsequently, tetramethylethylenediamine (0.1mL, 0.67mmol) and potassium persulfate (0.5g, 1.9mmol) were added to solution B and stirred for 2min, and then the mixture was placed in an oven and polymerized at 50℃ for 3h to obtain a hydrogel. The hydrogel was then cultured in distilled water for 7 days, with water changed every day, and finally H2TiO3@PAM was obtained, labeled as HTO@PAM-6, the mass fraction of H2TiO3 was 24% of the total mass of the composite hydrogel, and its tensile strength was 0.121MPa.

[0066] (2) Adsorption test

[0067] 1 g H2TiO3@PAM-6 was placed in a solution containing Li at pH 8 at 25 °C. + 、Na + , Ca 2+ , K + and Mg 2+ The adsorption selectivity and saturated adsorption capacity of lithium ions were determined in 1L of salt lake brine containing ions. The initial concentrations of ions in the salt lake brine were C Li+ =116.78mg·L -1 ,C Na+ =99.45mg·L -1 ,C Ca2+ =98.65mg·L -1 ,C K+ =100.72mg·L -1 and C Mg2+ =99.73mg·L -1 .

[0068] Figure 6 The stress-strain curve of the material. The maximum elongation at break of H2TiO3@PAM-6 is 337.3%, and the peak tensile strength is 0.121MPa.

[0069] Example 7

[0070] (1) Preparation of H2TiO3@PAM

[0071] 50g of H2TiO3 suspension with a mass fraction of 30% was placed in a beaker (solution A). Then sodium alginate (0.15g, 0.68mmol) was added to solution A and stirred for 15min, and then acrylamide (8g, 112.55mmol) and N,N'-methylenebisacrylamide (0.05g, 0.30mmol) were added at the same time and stirred for another 10min to obtain solution B. Subsequently, tetramethylethylenediamine (0.1mL, 0.67mmol) and potassium persulfate (0.5g, 1.9mmol) were added to solution B and stirred for 2min, and then the mixture was placed in an oven and polymerized at 50℃ for 3h to obtain a hydrogel. The hydrogel was then cultured in distilled water for 7 days, with water changed every day, and finally H2TiO3@PAM was obtained, labeled as HTO@PAM-7, the mass fraction of H2TiO3 was 24% of the total mass of the composite hydrogel, and its tensile strength was 0.076MPa.

[0072] (2) Adsorption test

[0073] 1 g H2TiO3@PAM-7 was placed in a solution containing Li at pH 8 at 25 °C. + 、Na + , Ca 2+ , K + and Mg 2+ The adsorption selectivity and saturated adsorption capacity of lithium ions were determined in 1L of salt lake brine containing ions. The initial concentrations of ions in the salt lake brine were C Li+ =116.78mg·L -1 ,C Na+ =99.45mg·L -1 ,C Ca2+ =98.65mg·L -1 ,C K+ =100.72mg·L -1 and C Mg2+ =99.73mg·L -1 .

[0074] Figure 6 The stress-strain curve of the material. The maximum elongation at break of H2TiO3@PAM-7 is 81.2%, and the peak tensile strength is 0.076MPa.

[0075] Example 8

[0076] (1) Preparation of H2TiO3@PAM

[0077] 50g of H2TiO3 suspension with a mass fraction of 30% was placed in a beaker (solution A). Then sodium alginate (0.15g, 0.68mmol) was added to solution A and stirred for 15min, and then acrylamide (8g, 112.55mmol) and N,N'-methylenebisacrylamide (0.07g, 0.45mmol) were added at the same time and stirred for another 10min to obtain solution B. Subsequently, tetramethylethylenediamine (0.1mL, 0.67mmol) and potassium persulfate (0.5g, 1.9mmol) were added to solution B and stirred for 2min, and then the mixture was placed in an oven and polymerized at 50℃ for 3h to obtain a hydrogel. The hydrogel was then cultured in distilled water for 7 days, with water changed every day, and finally H2TiO3@PAM was obtained, labeled as HTO@PAM-8, the mass fraction of H2TiO3 was 24% of the total mass of the composite hydrogel, and its tensile strength was 0.052MPa.

[0078] (2) Adsorption test

[0079] 1 g H2TiO3@PAM-8 was placed in a solution containing Li at pH 8 at 25 °C. + 、Na + , Ca 2+ , K + and Mg 2+ The adsorption selectivity and saturated adsorption capacity of lithium ions were determined in 1L of salt lake brine containing ions. The initial concentrations of ions in the salt lake brine were C Li+ =116.78mg·L -1 ,C Na+ =99.45mg·L -1 ,C Ca2+ =98.65mg·L -1 ,C K+ =100.72mg·L -1 and C Mg2+ =99.73mg·L -1 .

[0080] Figure 6 The stress-strain curve of the material. The maximum elongation at break of H2TiO3@PAM-8 is 47.68%, and the peak tensile strength is 0.052MPa.

[0081] Example 9

[0082] (1) Preparation of H2TiO3@PAM

[0083] 50g of H2TiO3 suspension with a mass fraction of 30% was placed in a beaker (solution A). Then sodium alginate (0.15g, 0.68mmol) was added to solution A and stirred for 15min, and then acrylamide (8g, 112.55mmol) and N,N'-methylenebisacrylamide (0.03g, 0.19mmol) were added at the same time and stirred for another 10min to obtain solution B. Tetramethylethylenediamine (0.1mL, 0.67mmol) and potassium persulfate (1.5g, 5.7mmol) were then added to solution B and stirred for 2min. The mixture was then placed in an oven and polymerized at 50°C for 3h to obtain a hydrogel. The hydrogel was then cultured in distilled water for 7 days, with the water changed every day, and finally H2TiO3@PAM was obtained, labeled as HTO@PAM-9. The mass fraction of H2TiO3 was 24% of the total mass of the composite hydrogel, and its tensile strength was 0.051MPa.

[0084] (2) Adsorption test

[0085] 1 g H2TiO3@PAM-9 was placed in a solution containing Li at pH 8 at 25 °C. + 、Na + , Ca 2+ , K + and Mg 2+ The adsorption selectivity and saturated adsorption capacity of lithium ions were determined in 1L of salt lake brine containing ions. The initial concentrations of ions in the salt lake brine were C Li+ =116.78mg·L -1 ,C Na+ =99.45mg·L -1 ,C Ca2+ =98.65mg·L -1 ,C K+ =100.72mg·L -1 and C Mg2+ =99.73mg·L -1 .

[0086] Example 10

[0087] (1) Preparation of H2TiO3@PAM

[0088] 50g of H2TiO3 suspension with a mass fraction of 30% was placed in a beaker (solution A). Then sodium alginate (0.15g, 0.68mmol) was added to solution A and stirred for 15min, and then acrylamide (8g, 112.55mmol) and N,N'-methylenebisacrylamide (0.03g, 0.19mmol) were added at the same time and stirred for another 10min to obtain solution B. Tetramethylethylenediamine (0.1mL, 0.67mmol) and potassium persulfate (0.5g, 1.9mmol) were then added to solution B and stirred for 2min. The mixture was then placed in an oven and polymerized at 20°C for 5h to obtain a hydrogel. The hydrogel was then cultured in distilled water for 7 days, with water changed every day, and finally H2TiO3@PAM was obtained, labeled as HTO@PAM-10. The mass fraction of H2TiO3 was 24% of the total mass of the composite hydrogel, and its tensile strength was 0.182MPa.

[0089] (2) Adsorption test

[0090] 1 g H2TiO3@PAM-10 was placed in a solution containing Li at pH 8 at 25 °C. + 、Na + , Ca 2+ , K + and Mg 2+ The adsorption selectivity and saturated adsorption capacity of lithium ions were determined in 1L of salt lake brine containing ions. The initial concentrations of ions in the salt lake brine were C Li+ =116.78mg·L -1 ,C Na+ =99.45mg·L -1 ,C Ca2+ =98.65mg·L -1 ,C K+ =100.72mg·L -1 and C Mg2+ =99.73mg·L -1 .

[0091] Embodiment 11

[0092] (1) Preparation of H2TiO3@PAM

[0093] 50g of H2TiO3 suspension with a mass fraction of 30% was placed in a beaker (solution A). Then sodium alginate (0.15g, 0.68mmol) was added to solution A and stirred for 15min, and then acrylamide (8g, 112.55mmol) and N,N'-methylenebisacrylamide (0.03g, 0.19mmol) were added at the same time and stirred for another 10min to obtain solution B. Tetramethylethylenediamine (0.1mL, 0.67mmol) and potassium persulfate (0.5g, 1.9mmol) were then added to solution B and stirred for 2min. The mixture was then placed in an oven and polymerized at 70℃ for 3h to obtain a hydrogel. The hydrogel was then cultured in distilled water for 7 days, with water changed every day, and finally H2TiO3@PAM was obtained, labeled as HTO@PAM-11. The mass fraction of H2TiO3 was 24% of the total mass of the composite hydrogel, and its tensile strength was 0.143MPa.

[0094] (2) Adsorption test

[0095] 1 g H2TiO3@PAM-11 was placed in a solution containing Li at pH 8 at 25 °C. + 、Na + , Ca 2+ , K + and Mg 2+ The adsorption selectivity and saturated adsorption capacity of lithium ions were determined in 1L of salt lake brine containing ions. The initial concentrations of ions in the salt lake brine were C Li+ =116.78mg·L -1 ,C Na+ =99.45mg·L -1 ,C Ca2+ =98.65mg·L -1 ,C K+ =100.72mg·L -1 and C Mg2+ =99.73mg·L -1 .

[0096] Example 12

[0097] (1) Preparation of H2TiO3@PAM

[0098] 50g of H2TiO3 suspension with a mass fraction of 30% was placed in a beaker (solution A). Then sodium alginate (0.15g, 0.68mmol) was added to solution A and stirred for 15min, and then acrylamide (8g, 112.55mmol) and N,N'-methylenebisacrylamide (0.03g, 0.19mmol) were added at the same time and stirred for another 10min to obtain solution B. Subsequently, triethanolamine (0.09mL, 0.67mmol) and sodium persulfate (0.44g, 1.9mmol) were added to solution B and stirred for 2min, and then the mixture was placed in an oven and polymerized at 50℃ for 3h to obtain a hydrogel. The hydrogel was then cultured in distilled water for 7 days, with water changed every day, and finally H2TiO3@PAM was obtained, labeled as HTO@PAM-12, the mass fraction of H2TiO3 was 24% of the total mass of the composite hydrogel, and its tensile strength was 0.171MPa.

[0099] (2) Adsorption test

[0100] 1 g H2TiO3@PAM-12 was placed in a solution containing Li at pH 8 at 25 °C. + 、Na + , Ca 2+ , K + and Mg 2+ The adsorption selectivity and saturated adsorption capacity of lithium ions were determined in 1L of salt lake brine containing ions. The initial concentrations of ions in the salt lake brine were C Li+ =116.78mg·L -1 ,C Na+ =99.45mg·L -1 ,C Ca2+ =98.65mg·L -1 ,C K+ =100.72mg·L -1 and C Mg2+ =99.73mg·L -1 .

[0101] Example 13

[0102] (1) Preparation of H2TiO3@PAM

[0103] 50g of H2TiO3 suspension with a mass fraction of 30% was placed in a beaker (solution A). Then polyvinyl alcohol (0.25g, 5.68mmol) was added to solution A and stirred for 15min, and then acrylamide (8g, 112.55mmol) and N,N'-methylenebisacrylamide (0.03g, 0.19mmol) were added at the same time and stirred for another 10min to obtain solution B. Subsequently, tetramethylethylenediamine (0.1mL, 0.67mmol) and ammonium persulfate (0.43g, 1.9mmol) were added to solution B and stirred for 2min, and then the mixture was placed in an oven and polymerized at 50℃ for 3h to obtain a hydrogel. The hydrogel was then cultured in distilled water for 7 days, with water changed every day, and finally H2TiO3@PAM was obtained, labeled as HTO@PAM-13, the mass fraction of H2TiO3 was 24% of the total mass of the composite hydrogel, and its tensile strength was 0.165MPa.

[0104] (2) Adsorption test

[0105] 1 g H2TiO3@PAM-13 was placed in a solution containing Li at pH 8 at 25 °C. + 、Na + , Ca 2+ , K + and Mg 2+ The adsorption selectivity and saturated adsorption capacity of lithium ions were determined in 1L of salt lake brine containing ions. The initial concentrations of ions in the salt lake brine were C Li+ =116.78mg·L -1 ,C Na+ =99.45mg·L -1 ,C Ca2+ =98.65mg·L -1 ,C K+ =100.72mg·L -1 and C Mg2+ =99.73mg·L -1 .

[0106] Embodiment 14

[0107] (1) Preparation of H2TiO3@PAM

[0108] 50g of H2TiO3 suspension with a mass fraction of 30% was placed in a beaker (solution A). Then chitosan (0.25g, 1.55mmol) was added to solution A and stirred for 15min, and then acrylamide (8g, 112.55mmol) and N,N'-methylenebisacrylamide (0.03g, 0.19mmol) were added at the same time and stirred for another 10min to obtain solution B. Tetramethylethylenediamine (0.1mL, 0.67mmol) and potassium persulfate (0.5g, 1.9mmol) were then added to solution B and stirred for 2min. The mixture was then placed in an oven and polymerized at 50°C for 5h to obtain a hydrogel. The hydrogel was then cultured in distilled water for 7 days, with the water changed every day, and finally H2TiO3@PAM was obtained, labeled as HTO@PAM-14. The mass fraction of H2TiO3 was 24% of the total mass of the composite hydrogel, and its tensile strength was 0.183MPa.

[0109] (2) Adsorption test

[0110] 1 g H2TiO3@PAM-14 was placed in a solution containing Li at pH 8 at 25 °C. + 、Na + , Ca 2+ , K + and Mg 2+ The adsorption selectivity and saturated adsorption capacity of lithium ions were determined in 1L of salt lake brine containing ions. The initial concentrations of ions in the salt lake brine were C Li+ =116.78mg·L -1 ,C Na+ =99.45mg·L -1 ,C Ca2+ =98.65mg·L -1 ,C K+ =100.72mg·L -1 and C Mg2+ =99.73mg·L -1 .

[0111] Embodiment 15

[0112] (1) Preparation of H2TiO3@PAM

[0113] 50g of H2TiO3 suspension with a mass fraction of 30% was placed in a beaker (solution A). Then sodium alginate (0.15g, 0.68mmol) was added to solution A and stirred for 15min, and then acrylamide (7g, 98.49mmol) and N,N'-methylenebisacrylamide (0.03g, 0.19mmol) were added at the same time and stirred for another 10min to obtain solution B. Tetramethylethylenediamine (0.1mL, 0.67mmol) and potassium persulfate (0.5g, 1.9mmol) were then added to solution B and stirred for 2min. The mixture was then placed in an oven and polymerized at 50°C for 5h to obtain a hydrogel. The hydrogel was then cultured in distilled water for 6 days, with water changed every day, and finally H2TiO3@PAM was obtained, labeled as HTO@PAM-15. The mass fraction of H2TiO3 was 24% of the total mass of the composite hydrogel, and its tensile strength was 0.174MPa.

[0114] (2) Adsorption test

[0115] 1 g H2TiO3@PAM-15 was placed in a solution containing Li at pH 8 at 25 °C. + 、Na + , Ca 2+ , K + and Mg 2+ The adsorption selectivity and saturated adsorption capacity of lithium ions were determined in 1L of salt lake brine containing ions. The initial concentrations of ions in the salt lake brine were C Li+ =116.78mg·L -1 ,C Na+ =99.45mg·L -1 ,C Ca2+ =98.65mg·L -1 ,C K+ =100.72mg·L -1 and C Mg2+ =99.73mg·L -1 .

[0116] Example 16

[0117] (1) Preparation of H2TiO3@PAM

[0118] 50g of H2TiO3 suspension with a mass fraction of 30% was placed in a beaker (solution A). Then sodium alginate (0.15g, 0.68mmol) was added to solution A and stirred for 15min, and then acrylamide (9g, 126.64mmol) and N,N'-methylenebisacrylamide (0.03g, 0.19mmol) were added at the same time and stirred for another 10min to obtain solution B. Tetramethylethylenediamine (0.1mL, 0.67mmol) and potassium persulfate (0.5g, 1.9mmol) were then added to solution B and stirred for 2min. The mixture was then placed in an oven and polymerized at 50°C for 5h to obtain a hydrogel. The hydrogel was then cultured in distilled water for 8 days, with the water changed every day, and finally H2TiO3@PAM was obtained, labeled as HTO@PAM-16. The mass fraction of H2TiO3 was 24% of the total mass of the composite hydrogel, and its tensile strength was 0.186MPa.

[0119] (2) Adsorption test

[0120] 1 g H2TiO3@PAM-16 was placed in a solution containing Li at pH 8 at 25 °C. + 、Na + , Ca 2+ , K + and Mg 2+ The adsorption selectivity and saturated adsorption capacity of lithium ions were determined in 1L of salt lake brine containing ions. The initial concentrations of ions in the salt lake brine were C Li+ =116.78mg·L -1 ,C Na+ =99.45mg·L -1 ,C Ca2+ =98.65mg·L -1 ,C K+ =100.72mg·L -1 and C Mg2+ =99.73mg·L -1 .

[0121] Evaluation of the adsorption capacity Q of H2TiO3@PAM as a composite lithium ion sieve t , equilibrium adsorption time Adsorption selectivity in salt lake brine

[0122] Application Example 1

[0123] (1) Adsorption capacity Q t and adsorption equilibrium time test:

[0124] 1g H2TiO3@PAM was added into 1L LiOH solution (100mg·L-1 ) and the stirring time was determined. Then ICP (inductively coupled plasma) was used to measure the Li + The initial concentration (C0) and instantaneous concentration (C t ), C t Until the concentration does not change much over time. The adsorption capacity of H2TiO3@PAM is Q t Calculated by formula (1).

[0125]

[0126] (2) Adsorption cycle test (calculated based on 80% attenuation of adsorption capacity):

[0127] 1g H2TiO3@PAM was dissolved in LiOH solution (100mg·L -1 ) in the cycling performance, the adsorption of Li2TiO3@PAM was carried out by acid washing with 0.2 mol mg·L -1 After that, conduct adsorption experiment to see the attenuation of adsorption capacity. The calculation formula of test conditions is the same as formula (1).

[0128] (3) Adsorption selectivity test (with Li + Mg 2+ Separation factor is the content of investigation):

[0129] At 25 °C, 1 g of H2TiO3@PAM was placed in a solution containing Li + 、Na + , Ca 2+ , K + and Mg 2+ The adsorption selectivity of ions in salt lake brine for 24 h (the ion concentrations correspond to 113.48, 99.24, 100.55, 99.63, 101.69 mg·L -1 ). Using ICP to measure Li + The initial concentration (C0) and instantaneous concentration (C t ). Partition coefficient (K d ) and separation factor They are calculated by formulas (2) and (3) respectively.

[0130]

[0131] The experimental results of the application example are shown in Table 1

[0132] Table 1 Application example experimental results

[0133]

[0134]

Claims

1. A composite hydrogel lithium ion sieve, characterized in that: The composite hydrogel lithium ion sieve uses polyacrylamide PAM as a binder, and the powdered active component H2TiO3 is embedded in PAM, wherein the mass fraction of H2TiO3 in H2TiO3@PAM is 13.8%-24%.

2. A method for preparing the composite hydrogel lithium ion sieve as claimed in claim 1, wherein the specific steps are: H2TiO3 and deionized water are added to a beaker and stirred evenly to obtain a suspension; then, a viscosity modifier is added to the suspension, stirred, and acrylamide and N,N'-methylenebisacrylamide are added at the same time, and a catalyst and an initiator are added after stirring. After stirring evenly, the mixture is placed in an oven for heating and polymerization to obtain a composite hydrogel; the hydrogel is then cultured in distilled water to obtain H2TiO3@PAM.

3. The method according to claim 2, characterized in that The mass fraction of H2TiO3 in the suspension is 16%-30%.

4. The method according to claim 2, characterized in that: The viscosity modifier is polyvinyl alcohol, chitosan or sodium alginate; the mass ratio of the viscosity modifier to the suspension is (0.002-0.010):

1.

5. The method according to claim 2, characterized in that: The mass ratio of acrylamide to suspension is (0.14-0.18):

1.

6. The method according to claim 2, characterized in that The molar ratio of the N,N'-methylenebisacrylamide to acrylamide is (0.0005-0.0040):

1.

7. The method according to claim 2, characterized in that The initiator is potassium persulfate, sodium persulfate, or ammonium persulfate; the molar ratio of the initiator to acrylamide is (0.015-0.051):

1.

8. The method according to claim 2, characterized in that: The catalyst is triethanolamine and tetramethylethylenediamine; the molar ratio of the catalyst to acrylamide is (0.005-0.007):

1.

9. The method according to claim 2, characterized in that: The polymerization reaction temperature is (20-70)°C, and the reaction time is 3-5h.

10. The method according to claim 2, characterized in that The cells were cultured in distilled water for 6-8 days.

Citation Information

Patent Citations

  • Method for synthesizing porous spherical lithium titanate

    CN102557121A

  • Sodium alginate-acrylamide composite aquagel, and preparation method and application thereof

    CN105504166A

  • Preparation method for hydrophilic spherical composite lithium-ion sieve adsorbent

    CN111185139A

  • Lithium ion sieve nanofiber felt and preparation method thereof

    CN115874356A

  • Modified lithium ion sieve as well as preparation method and application thereof

    CN118491473A

Cited By

  • Preparation method of super-hydrophilic material, super-hydrophilic material and application of super-hydrophilic material

    CN120227859A